Romania : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Romania's Request for a Stand-By Arrangement (SBA). Since the 2008 global financial crisis, Romania has made significant progress in reducing macroeconomic imbalances and rebuilding fiscal and financial buffers. However, Romania remains vulnerable to external shocks, in particular uncertainties in the euro area as well as global volatility in capital flows to emerging markets. The new SBA would provide a valuable policy anchor and support Romania's comprehensive economic program for 2013-2015 to maintain sound macroeconomic policies and financial sector stability and continue structural reforms to enhance growth prospects. The IMF staff supports the authorities' request for a new SBA.